Nastoletnie macierzyństwo – szansa czy ograniczenie? Doświadczenia małoletnich matek z grup defaworyzowanych - Skowrońska-Pućka, Agnieszka (Studia Edukacyjne, 2020)
This article deals with the issues of early motherhood. Early parenting is a critical event in the life of teenage girls. Teens are mentally and socially immature and unprepared to fulfill the role of mother. Besides minor mothers usually come from poor families, are pupils in primary or secondary schools, do not work, do not have a steady income and own apartment, and in this case remain under the custody care and educational institution. The article is an attempt to answer the question, as teenagers from disadvantaged groups, pupil of childcare centers and describe the experience of motherhood. What is surprising, despite initial concerns and difficulties in retrospect evaluate them as a gift and a blessing, a source of valuable life experience and even a protective factor against the occurrence of other problems care and education.